Phase III trial of vandetanib compared with erlotinib in patients with previously trreated advanced non-small-cell lung cancer - Natale, Ronald B.; Thongprasert, Sumitra; Greco, F. Anthony; Thomas, Michael; Tsai, Chun-Ming; Sunpaweravong, Patrapim; Ferry, David; Mulatero, Clive; Whorf, Robert; Thompson, Joyce; Barlesi, Fabrice; Langmuir, Peter; et al. (Journal of clinical oncology, 2011)
Purpose - - Vandetanib is a once-daily oral inhibitor of vascular endothelial growth factor receptor and epidermal growth factor receptor signaling. This phase III study assessed the efficacy of vandetanib versus erlotinib in unselected patients with advanced non-small-cell lung cancer (NSCLC) after treatment failure with one to two prior cytotoxic chemotherapy regimens. - - Patients and Methods - - One thousand two hundred forty patients were randomly assigned to receive vandetanib 300 mg/d (n = 623) or erlotinib 150 mg/d (n = 617). The primary objective was to show superiority in progression-free survival (PFS) for vandetanib versus erlotinib. If the difference did not reach statistical significance for superiority, a noninferiority analysis was conducted. - - Results - - There was no significant improvement in PFS for patients treated with vandetanib versus erlotinib (hazard ratio [HR], 0.98; 95.22% CI, 0.87 to 1.10; P = .721); median PFS was 2.6 months for vandetanib and 2.0 months for erlotinib. There was also no significant difference for the secondary end points of overall survival (HR, 1.01; P = .830), objective response rate (both 12%), and time to deterioration of symptoms for pain (HR, 0.92; P = .289), dyspnea (HR, 1.07; P = .407), and cough (HR, 0.94; P = .455). Both agents showed equivalent PFS and overall survival in a preplanned noninferiority analysis. Adverse events (AEs; any grade) more frequent with vandetanib than erlotinib included diarrhea (50% v 38%, respectively) and hypertension (16% v 2%, respectively); rash was more frequent with erlotinib than vandetanib (38% v 28%, respectively). The overall incidence of grade ≥ 3 AEs was also higher with vandetanib than erlotinib (50% v 40%, respectively). - - Conclusion - - In patients with previously treated advanced NSCLC, vandetanib showed antitumor activity but did not demonstrate an efficacy advantage compared with erlotinib. There was a higher incidence of some AEs with vandetanib.
Gesehen am 21.09.2022